Modular switched mode power supply, tested with DC motor load. (19th March 2020) - Srinivas, K.N.; Ramkumar, M.
A modular switched power supply fit to be used as a standby supply in the electrical laboratories or in the industrial work floors is proposed in this paper. Conventional switched power supply involves bulk transformers. Various disadvantages arise due to this bulkiness. This work makes an attempt to address this issue and proposes a solid state switched power supply. The description of the proposed circuit, simulation of its operation and the working model are presented.